GAMBARAN KETUBAN PECAH DINI, WARNA KETUBAN JELEK DAN INFEKSI IBU DENGAN KEJADIAN INFEKSI PADA BAYI BARU LAHIR DI RSUD ABDUL WAHAB SJAHRANIE SAMARINDA - Rizkiannur Putri, Amalia; Sukartini; Fitriany, Evi (Sekolah Tinggi Ilmu Kesehatan Mutiara Mahakam, 2020)
The early 28 days of life called the neonatal period is the most vulnerable period for infants. The infants face the highest risk of death in the first month after birth. The most common cause of infant death is asphyxia, prematurity, and infection. Infection in newborns is defined as a condition where the newborns have a disease caused by microorganisms. One of the risk factors causing infection in newborns includes factors from the mother, such as premature rupture of membranes, green or meconium and smelly amniotic fluid, maternal infection, and others. The main objective of this research was to describe the risk factors of incidence of infection in newborns at RSUD Abdul Wahab Sjahranie Samarinda. This research uses a retrospective descriptive method with the cross-sectional approach. Sampling was done by taking data on medical records of patients at the RSUD Abdul Wahab Sjahranie Medical Record Installation using total sampling technique. The results obtained were 99 samples that met the inclusion and exclusion criteria with details of patients who experienced premature rupture of membranes by 18 people (18,2%), poor amniotic color by 62 people (62,6%), mothers who had leukocytosis by 15 people (15,2%), and the incidence of infection in newborns by 2 people (2%). the collected data were tabulated bu frequency and percentage and displayed in tables